Utilisation of Roselle (Hibiscus Sabdariffa, L) By-Products as Roughage Feed for Sheep - Tri Hesti Wahyuni (2000)
Roselle (Hibiscus sabdariffa, L.) is cultivated for the calyces, which are used for making roselle juice, a drink known to be high in vitamin C. The leaves are also used as a pot herb and some varieties are grown for their fibre. Roselle pods and seeds are by-products obtained after the calyces are removed from the fruits. The objective of the study was utilised the roselle by-products for small ruminant especially as sheep feed. Roselle by-products were obtained from farmers in Terengganu. In the first part of the study, chemical analysis was performed on the whole pods, seeds and empty pods. The roselle by-products were found to be high in protein, fat and fibre. The nutrient content of roselle byproducts was higher than other agricultural by-products, such as sago waste, straw, cocoa pods, stalks and sugar cane bagasse. In the second part of the study, in situ degradability of roselle empty pods and seeds was investigated. The result indicated that degradation of dry matter and organic matter of roselle seeds was higher than roselle empty pods, significantly different (P< 0.01) in 48 hours, percentage of DM and OM of roselle seeds and empty pods were 36.38%, 28.36% and 23.01%, 17.66%, respectively; and also in 72 hours by 39.87%, 31 % and 26.30%, 20.85%, respectively. Even though the seeds were more degradable than the empty pods, both were still low in degradability « 50%). Degradability of roselle by-products can be improved by using chemical treatment, physical treatment or microbial treatment. In the third part of the study, roselle by-products were treated with soaked alkali such as NaOH and Ca(OHh at various levels (2%, 4% and 6%), and the nutrient contents analysed. It was found that the chemical composition of roselle treated with NaOH and Ca(OH)2 decreased, except for ash.